A single-blind randomized controlled trial of celiac plexus block for analgesia after whipple surgery - Minpu Li; Lili Fang; Taotao Xing; Chenyang Wang; Shuyi Chen; Shui Yu; Jiali Zhu (BMC Anesthesiology)
Abstract Background Effective management of both incisional and visceral postoperative pain during open abdominal surgery is crucial for patient recovery. This study evaluated the effect of celiac plexus block on postoperative pain and recovery. Methods This single-center, patient-assessor-blinded, blank-controlled randomized clinical trial was conducted from March 9, 2022, to November 12, 2023. A total of 78 patients scheduled for open Whipple surgery were randomized. The intervention involved either receiving a celiac plexus block (Group NB) with 20 ml of 0.5% ropivacaine during surgery or not receiving the block (Group GC). Both groups received traditional postoperative analgesia. The primary outcome was opioid consumption within 72 h post-surgery. Secondary outcomes included the frequency of analgesic pump presses, pain scores, hemodynamic parameters before and after nerve block as well as postoperatively, levels of postoperative inflammatory markers, time to first flatus, length of postoperative hospital stay, and perioperative complications. Results Among the 78 patients enrolled, 37 were randomized to receive intraoperative celiac plexus block and 41 were not. In total, 12 patients (8 in group GC and 4 in group NB) were excluded because of protocol deviations, and 66 patients (33 in each group) were included in the per-protocol analysis. Group NB demonstrated significantly lower total opioid consumption within the first 72 h post-surgery than group GC (mean (SD), 66 (18.8) mg vs. 88.9 (21.2) mg, respectively; P < 0.01). Pain scores assessed using the Visual Analog Scale were consistently lower in group NB at all postoperative time points (all P < 0.05). The first press of the patient-controlled analgesia (PCA) pump occurred significantly later, and the daily frequency of PCA pump presses was lower in group NB. The time to first flatus and length of postoperative stay were shorter in group NB but not statistically significant. Only inflammatory markers showed significantly lower C-reactive protein (CRP) levels in group NB at 24 h postoperatively. Hemodynamic monitoring results indicated that it had a minor impact. Conclusion We confirmed that the direct-vision intraoperative celiac plexus block is a safe and effective procedure that significantly reduces postoperative opioid consumption and pain scores. Further studies with larger sample sizes are warranted to confirm these findings and explore long-term outcomes. Trial registration Clinical Trial Registry Identifier: NCT05205720. Registered on January 25, 2022.